2016
DOI: 10.1016/j.nbd.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane-induced inactivation of CREB through histone deacetylase 4 is responsible for cognitive impairment in developing brain

Abstract: Anesthetics including isoflurane are known to induce neuronal dysfunction in the developing brain, however, the underlying mechanism is mostly unknown. The transcriptional activation of CREB (cyclic AMP response element binding protein) and the alterations in acetylation of histones modulated by several histone deacetylases such as HDAC4 (histone deacetylase 4) are known to contribute to synaptic plasticity in the brain. Here we have shown that administration of isoflurane (1.4%) for 2h leads to transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In the present study, we observed reduced levels of PKA-Cα and p-CREB on days 14 and 28 after exposure to isoflurane. This observation is consistent with a previous study that reported the inactivation of CREB by isoflurane, thus resulting in the loss of dendritic outgrowth and the reduced expression of proteins that are essential for memory and cognitive functions in the brains of P7 mice, including BDNF and c-fos 32 . In contrast, in our present study, we found that the levels of PKA-Cα and p-CREB remained unchanged following exposure to sevoflurane.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed reduced levels of PKA-Cα and p-CREB on days 14 and 28 after exposure to isoflurane. This observation is consistent with a previous study that reported the inactivation of CREB by isoflurane, thus resulting in the loss of dendritic outgrowth and the reduced expression of proteins that are essential for memory and cognitive functions in the brains of P7 mice, including BDNF and c-fos 32 . In contrast, in our present study, we found that the levels of PKA-Cα and p-CREB remained unchanged following exposure to sevoflurane.…”
Section: Discussionsupporting
confidence: 93%
“…Growing evidence indicates that HDAC4 may contribute to neurogenesis via regulating the expression and function of multiple molecules. First, HDAC4 regulates the activity and expression of cAMP response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF), respectively, which play a key role in neurogenesis after ischemic stroke [ 18 20 , 78 ] (Fig. 1 ).…”
Section: The Role Of Hdac4 In Ischemic Stroke and Underlying Mechanismentioning
confidence: 99%
“…However, nuclear shuttling of HDAC4 suppresses the transcriptional activity of CREB by reducing the interaction among acetyltransferase, CBP, and CREB, leading to the reduction of BDNF. [ 18 20 ]. In addition, HDAC4 might be another key mediator of the effect of miRNA-9 on neurogenesis in ischemic stroke as HDAC4 is the target of miRNA-9 [ 77 , 79 ].…”
Section: The Role Of Hdac4 In Ischemic Stroke and Underlying Mechanismentioning
confidence: 99%
“…A decrease in the interaction between CBP and CREB has also been reported in the brains of postnatal mice with isoflurane-induced cognitive impairments, resulting from an increase in nuclear translocation of HDAC4. HDAC4 interacts with CREB in the nucleus, which results in an impairment in transcriptional activation of CREB and a decrease in the expression levels of BDNF and c-Fos ( Sen and Sen, 2016 ). In an isoflurane-exposed maternal-fetal rat model, overexpression of HDAC2 induced the subsequent downregulation of CREB and was associated with spatial learning and memory impairments in the offspring ( Luo et al, 2016 ).…”
Section: Epigenetic Changes and Therapeutic Approaches For Anestheticmentioning
confidence: 99%